A parametric permeability study for a simplified vertebra based on regular microstructures. Issue 1 (12th November 2019) - Trivedi, Zubin; Bleiler, Christian; Wagner, Arndt; Röhrle, Oliver
Abstract: The following work focuses on studying the permeability and its dependency on geometric parameters on the macro‐scale representing the underlying microstructure. In particular, regular microstructures are studied such that the computation of permeability is straightforward and the geometric parameters can be modified in a systematic manner. The permeabilities of the respective geometries are then derived by numerical upscaling of pore‐scale velocities computed by using Abaqus' Stokes‐flow solver. Based on these results, the permeabilities were found to be strongly dependent on the specific surface area and the respective porosity. This indicates the potential to estimate the order of magnitude for the permeability of real‐word applications using these two parameters. Furthermore, the tortuosity can be beneficial to obtain better permeability estimations.